THE UTILIZATION OF PRESENTATION ACTIVITIES IN ONLINE SPEAKING CLASS - Ahsan Muzri S; A. Muliati; Geminastiti Sakkir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The objective of this research was to see the utilization of presentation activities in online speaking class. Pre-experimental design was adapted in this study. The respondents in this research were students in the eleventh grade at SMA Negeri 4 Sidrap academic year 2021//2022 through random sampling technique and XI IPA 1 was selected as the sample of this research. The instrument of this research was speaking test which was delivered as pre-test and post-test. The result shown that the utilization of presentation activities was significant to improve students’ speaking performance. It was proved that the students’ mean score of pre-tests was 5.72 and the students’ mean score of post-tests was 7.31 with percentage 28% of improvement. It could be concluded that the utilization of presentation activities in online speaking class can improve students speaking performance.